PTU-001 Diagnostic accuracy of non-invasive liver fibrosis markers in young adults within the ALSPAC population-based cohort. Issue 2 (June 2019) - Abeysekera, Kushala; Orr, James; Fernandes, Gwen; Hammerton, Gemma; Portal, Andrew; Heron, Jon; Gordon, Fiona; Hickman, Matthew
Abstract : Introduction: Early identification of non-alcoholic fatty liver disease (NAFLD) and alcohol-related liver disease (ARLD) can potentially halt progression to cirrhosis by removing the insult. Concerns remain regarding diagnostic accuracy of non-invasive fibrosis scores in extremes of age. This study aimed to evaluate diagnostic accuracy of non-invasive fibrosis scores in young adults within the Avon Longitudinal Study of Parents and Children (ALSPAC). Methods: 3864 study participants (SPs) (mean age 24 years; SD 0.8) underwent transient elastography (TE) using the Echosens Fibroscan 502 Touch®. Results with interquartile range/median ratio >30% were excluded. SPs with criteria for alcohol use disorder (AUD) or harmful daily alcohol intake were analysed separately; TE cut-off values assumed ARLD. All other SPs' TE results were interpreted using NAFLD TE cut-offs. Data was collated on TE result, body mass index, serology including alanine transaminase (ALT), aspartate aminotransferase (AST), platelet count, and fibrosis markers procollagen-3 N-terminal peptide (P3NP) and hyaluronic acid (HA). To differentiate between fibrosis (TE scores equivalent to ≥METAVIR F2) and normal results, receiver operator characteristics (ROC) were derived for the Southampton Traffic Light Test (STLT), AST/ALT ratio, AST to Platelet Ratio Index (APRI) score, Fibrosis (FIB)-4 score, P3NP and HA. Statistical analysis was performed using Stata MP 15.1. Results: 3600 TEs were eligible for analysis. 104 SPs (2.9%) had TE ≥7.5 kPa. 8 SPs with suspected NAFLD had TE ≥ 11.7 kPa, 1 SP with suspected ARLD had TE ≥ 12.5 kPa. 472 (13.1%) SPs gave a history of excessive daily alcohol consumption or AUD. Of this group, 5.7% had TE ≥7.5 kPa. No non-invasive scores or scores accurately identified ≥F2 equivalent TE (≥7.5 kPa) in all SPs (area under ROC (AUROC) range 0.37–0.65). These results were reflected when assessing AUROCs to detect ≥F2 equivalent fibrosis (≥7.9 kPa) in SPs with suspected NAFLD (AUROC range 0.39–0.64). In SPs with suspected ARLD, APRI had a modest diagnostic accuracy (AUROC 0.73); all other markers and scores performed poorly in diagnosing ≥F2 equivalent fibrosis (AUROC range 0.24 – 0.67, excluding APRI). Conclusions: Non-invasive fibrosis scores have limited corroboration with TE in diagnosing moderate ARLD or NAFLD fibrosis. A study limitation is fibrosis scores were not compared to gold standard liver biopsy, in the setting of a large population study of young healthy adults; results should be interpreted in this context. The Enhanced Liver Fibrosis (ELF) test was not analysed, however, P3NP and HA – 2 of the ELF constituents – had low AUROCs.